Scenario planning as an organisational change agent - Nicol, Paul (Curtin University, 2005)
The thesis was based on a unique opportunity to compare the perceptions of participants before and after a scenario planning project conducted in a water utility. The researcher was able to explore the perceptions of the participants of scenario planning as a change agent directly, and so address a concern in some of the literature that much of the body of knowledge on scenario planning has been filtered through the viewpoints of scenario planning practitioners. Through the use of an adapted grounded theory approach, the perceptions of the participants emerged independently of a pre-conceived theoretical framework and explanations of the outcomes of the process were developed from this data. As well, the assumptions behind the practice of scenario planning were explored and from this a theory for scenario planning was developed. This was effected while constant comparison of concepts emerging from the data was in progress and provided a theoretical framework for the discussion of the empirical research. In this case scenario planning was perceived more as an instrument than as an agent of change, with a role of setting a framework for the strategic conversation in the subsequent phases of the change initiative. The outcomes of the research illustrated that uncertainties internal to the organisation had affected the implementation of change. In particular the conceptual ecologies of people in the organisation were not explored in depth, and this perpetuated a driving force for the future of the organisation that was not merely uncertain but remained unknowable. It was concluded that whether a scenario planning project achieved its objectives was matter of perception, with evaluation differing depending on the viewpoint taken.Change of mind-set was not necessarily needed for a change of strategic direction, which could be explained using a political metaphor. However, for cultural change to be effected, there was a need for operatives to identify with it. It was concluded from this case that unless change and/or the change process were adapted to resonate with the world views of the operatives, it was unlikely it would become embedded in the organisation and may be resisted. Conceptual ecologies needed to be explored for this adaptation to occur.